2017
DOI: 10.1002/iub.1686
|View full text |Cite
|
Sign up to set email alerts
|

miR‐200c regulates endothelin‐1 induced PASMCs abnormal proliferation and apoptosis

Abstract: miR-200c is an antioncogene in multiple tumors. However, its function in the pathogenesis of pulmonary arterial hypertension (PAH) has not been thoroughly investigated nor understood. In this study, we discovered that miR-200c was able to substantially upregulate in pulmonary arterial smooth muscle cells (PASMCs) treated with endothelin-1 (ET-1). miR-200c also induced cell proliferation and suppressed cell apoptosis in PASMCs in vitro. However, miR-200c had no effect on G1/S/G2 transitions during the cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…MicroRNAs have cell-type specific roles (Guduric-Fuchs et al, 2012), and miR-200c is enriched in the brain, particularly in neurons, oligodendrocytes (Buller et al, 2012;Lau et al, 2008) and microglia (Tang et al, 2017;Yu et al, 2015). MiR-200c expression increases in response to oxidative stress (Lee et al, 2010; and suppresses MAP2 expression (Yuan et al, 2017). In the present study utilizing this novel complexing method we confirmed a high degree of co-localization with miR 200c and neurons and low miR-200c in astrocytes.…”
Section: Discussionsupporting
confidence: 77%
“…MicroRNAs have cell-type specific roles (Guduric-Fuchs et al, 2012), and miR-200c is enriched in the brain, particularly in neurons, oligodendrocytes (Buller et al, 2012;Lau et al, 2008) and microglia (Tang et al, 2017;Yu et al, 2015). MiR-200c expression increases in response to oxidative stress (Lee et al, 2010; and suppresses MAP2 expression (Yuan et al, 2017). In the present study utilizing this novel complexing method we confirmed a high degree of co-localization with miR 200c and neurons and low miR-200c in astrocytes.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, inhibition of miR-93 increased cell viability and suppresses cell apoptosis in glaucoma HTM cells (29). miR-200c and PTEN are both factors involved in regulating cell apoptosis (30,31). The present study demonstrated that the level of PTEN was negatively regulated by miR-200c-3p.…”
Section: Discussionmentioning
confidence: 99%
“…PR‐positive breast cancer cells show a better outcome than PR‐negative, which is probably supported by an increased miR‐30b/c expression (Croset et al, ; Van Asten et al, ). Additionally, in PR‐positive breast cancer, miR‐200c acts as an antioncogene and inhibits cell migration (Yuan et al, ). In line with this, the lifespan of patients with low amounts of miR‐200c is significantly reduced because of the missing impact of miR‐200c on PR expression (Tuomarila et al, 2014; http://targetcan.org).…”
Section: Progesterone and Prsmentioning
confidence: 99%